2021
DOI: 10.1016/j.eclinm.2021.101153
|View full text |Cite
|
Sign up to set email alerts
|

The feeling, embodiment and emotion of hallucinations in first episode psychosis: A prospective phenomenological visual-ecological study using novel multimodal unusual sensory experience (MUSE) maps

Abstract: Background: Research and practice typically focus upon unimodal hallucinations, especially auditory verbal hallucinations. Contemporary research has however indicated that voice-hearing may co-occur within a broader milieu of feelings, and multimodal hallucinations may be more common than previously thought. Methods: An observational design asked participants to prospectively document the feeling and modality of hallucinations for one week prior to an interview. Novel visual diary methods involving drawing, wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Consequently, sensorimotor dysfunction likely contributes to both affective and psychotic psychopathology (102). Our results regarding CMA to somatosensory dysconnectivity in patients with PS (+) and ITS(+) is in line with evidence showing heightened affective appraisal of sensory stimuli in psychosis (103) and suggests that sensory experiences manifest along the pathway between affective and psychotic symptoms. Overall, our results regarding contribution of CMA dysconnectivity to both PS and ITS, hint toward a key role of the CMA as a neurobiological substrate of affective pathway to psychosis.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, sensorimotor dysfunction likely contributes to both affective and psychotic psychopathology (102). Our results regarding CMA to somatosensory dysconnectivity in patients with PS (+) and ITS(+) is in line with evidence showing heightened affective appraisal of sensory stimuli in psychosis (103) and suggests that sensory experiences manifest along the pathway between affective and psychotic symptoms. Overall, our results regarding contribution of CMA dysconnectivity to both PS and ITS, hint toward a key role of the CMA as a neurobiological substrate of affective pathway to psychosis.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding accompanying symptoms, all types of hallucinations seem to be associated with other clinical features. Thus, the study of Melvin et al [57] reported clusters of emotional feelings associated with hallucinations which by order of frequency could be described as fear and anxiety; despair and powerlessness; abused and threat; frustration and anger; loneliness; stress and distress and worry. The same research highlighted co-occurring bodily feelings such as tension, pressure, agitation, chills, heaviness, and dizziness, across hallucination types identifiable, localized, specific, and communicable.…”
Section: Hallucinationsmentioning
confidence: 99%